Tuning of Nano-Based Materials for Embedding Into Low-Permeability Polyimides for a Featured Gas Separation - Castro-Muñoz, Roberto; Ahmad, Mohd Zamidi; Fíla, Vlastimil (Frontiers in Chemistry, 2020)
Several concepts of membranes have emerged at aiming the enhancement on the separation performance, as well as some other physico-chemical properties, of the existing membrane materials. One of these concepts is the well-known mixed matrix membranes (MMMs), which combine the features of inorganic (e.g. zeolites, metal-organic frameworks, graphene, and carbon-based materials) and polymeric (e.g. polyimides, polymers of intrinsic microporosity, polysulfone, cellulose acetate, among others) materials. To date, it is likely that such a concept has been widely explored and developed towards low permeable polyimides for gas separation, such as ODA, BTDA-DAPI, m-PDA, HBA, and some others. When dealing with the gas separation performance of polyimide-based MMMs, these membranes tend to display some deficiency according to the poor polyimide-filler compatibility, which has promoted the tuning of chemical properties of those filling materials. This approach has indeed enhanced the polymer-filler interfaces, providing synergic MMMs with superior gas separation performance. Herein, the goal of this review paper is to give a critical overview of the current insights in fabricating MMMs base on chemically modified filling nanomaterials and low permeable polyimides for selective gas separation. Special interest has been paid to the chemical modification protocols of the fillers (including good filler dispersion) and thus the relevant experimental results provoked by such approaches. Moreover, some principles, as well as the main drawbacks, occurring during the MMM preparation are also given.